Enhancing the Tolerance of Eggplant Grown under Salt Stress Conditions via Foliar Selenium Application - Isetemkheb; Maatkare (Global Journal of Plant and Soil Sciences, 2025)
One of the most dangerous effects of climate change in Egypt is sea level rise, which will make the northern Delta more salinized. It is highly desirable for present and future crops to be more tolerant of salinity. In order to assess the impact of selenium foliar treatments (0, 5, 10, 20, 30 μM Na2SeO3) on eggplant cultivated on sandy soil and irrigated with varying concentrations of saline water (0, 30, 60, 120 mM NaCl), the current experiment was conducted in the experimental station at the Agriculture Research Centre in Egypt during the summer months of 2014 and 2015. According to the findings, the Se supplement at a concentration of 20 μM had the greatest effects on eggplant production and vegetative growth over a range of irrigation water salinity levels. N, P, and K contents in eggplant leaves and fruits increased with increasing salinity, but K decreased due to some kind of antagonism with Na. Nevertheless, N, P, and K contents in leaves and fruits increased with increasing Se supplements up to 20 μM to be at higher concentrations, after which they decreased. The lowest value (0.52) for the K/Na ratio in leaves was obtained by treating ECw 13.5 dS m-1 without Se supplementation, while the maximum value (1.71) was obtained from treating Se 30 μM under 0 mM NaCl irrigation water. Additionally, the amount of chlorophyll in plant leaves rose as the salinity of the irrigation water increased, but it fell as the amount of Se supplements increased. The treatment of ECw 13.5 dS m-1 without Se supplements produced the maximum proline content in fresh leaves (51 mg g-1), while the control treatment produced the lowest (30.9 mg g-1).